Health Screening for Early Detection of Degenerative Diseases UD Ridho Salsa Workers - Nastiti Trikurniadewi; Nugrahadi Dwi Pasca Budiono (Institut Ilmu Kesehatan Nahdlatul Ulama Tuban, 2026)
Background: Degenerative diseases such as hypertension, diabetes mellitus, and dyslipidemia are the main causes of morbidity and mortality in the productive age group. These diseases often develop without clear initial symptoms, so many new cases are diagnosed at an advanced stage. Low worker awareness of the importance of regular health checks is one of the main factors that delay early detection, especially in the informal business sector. Method: The implementation of community service activities is in the form of discussions and direct practice. The subjects of the service are workers of UD Ridho Salsa in Gresik Regency. The screening includes measuring blood pressure, random blood sugar levels, and total cholesterol levels. The activity is complemented by health education and follow-up referrals for participants with abnormal test results. Data analysis is done descriptively and analytically. Result: Most of UD Ridho Salsa workers are categorized as hypertension, 70% workers, a small portion of UD Ridho Salsa workers are categorized as diabetes mellitus and cholesterol, 10% workers. Conclusion: Medical check-up at the workplace accompanied by education have proven effective as an effort to detect degenerative diseases early in workers. Integration of routine medical check-ups into occupational health programs is essential to prevent an increase in the burden of degenerative diseases in the future.